2020
DOI: 10.1016/j.radphyschem.2019.108521
|View full text |Cite
|
Sign up to set email alerts
|

DNA condensation with a boron-containing cationic peptide for modeling boron neutron capture therapy

Abstract: The amino acid derivative 4-borono-L-phenylalanine (BPA) has been used in the radiation medicine technique boron neutron capture therapy (BNCT). Here we have characterized its interaction with DNA when incorporated into a positively charged hexa-L-arginine peptide. This ligand binds strongly to DNA and induces its condensation, an effect which is attenuated at higher ionic strengths. The use of an additional tetra-L-arginine ligand enables the preparation of a DNA condensate in the presence of a negligible con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Such a decrease in ethidium fluorescence is evident in Figure . With the intercalating fluorescent dye BOBO-3, at a concentration large enough to be detectable by visible absorption, we found that the decrease in its fluorescence intensity produced by the ligand Ac-BPA-Arg 6 -NH 2 was not caused by its displacement from the DNA to which it had been bound before the addition of the ligand Figure reveals that this fluorescence attenuation does not take place at a lower concentration of BOBO-3.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Such a decrease in ethidium fluorescence is evident in Figure . With the intercalating fluorescent dye BOBO-3, at a concentration large enough to be detectable by visible absorption, we found that the decrease in its fluorescence intensity produced by the ligand Ac-BPA-Arg 6 -NH 2 was not caused by its displacement from the DNA to which it had been bound before the addition of the ligand Figure reveals that this fluorescence attenuation does not take place at a lower concentration of BOBO-3.…”
Section: Discussionmentioning
confidence: 87%
“…In the absence of the ligand, DNA (10 μg mL –1 ) features a positive band at 270 nm and a negative band at 245 nm. The ligand alone (10 μmol L –1 ) exhibits a positive band at 220–230 nm at the absorption of its aromatic ring . The combination of DNA and the ligand at these concentrations produces large physical effects (Figures –); the CD spectrum under these conditions reveals a decrease in intensity of the positive band at 270 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, many efforts are being made to include the chemical and biological aspects of the problem in MC calculations, such as the code developed within the Geant4-DNA Project [ 66 ] (TOPAS-nBio is a wrapper for the latter). A clear example of this is the work by Perry et al [ 67 ] to model the DNA damage produced by the high LET particles involved in BNCT. Anyway, these theoretical calculations must be compared with experimental verifications.…”
Section: Fundamental Aspects Of Bnctmentioning
confidence: 99%